Understanding arsenic metabolism through spectroscopic determination of arsenic in human urine. Issue 3 (2006) - Brima Brima, Eid I. Eid I.; Jenkins Jenkins, Richard O. Richard O.; Haris Haris, Parvez I. Parvez I.
Abstract : In this review we discuss a range of spectroscopic techniques that are currently used for analysis of arsenic in human urine for understanding arsenic metabolism and toxicity, especially in relation to genetics/ethnicity, ingestion studies and exposure to arsenic through drinking water and diet. Spectroscopic techniques used for analysis of arsenic in human urine include inductively coupled plasma mass spectrometry (ICP-MS), hydride generation atomic absorption spectrometry (HG-AAS), hydride generation atomic fluorescence spectrometry (HG-AFS), graphite furnace atomic absorption spectrometry (GF-AAS) and liquid chromatography mass spectrometry (LC-MS). Advantages and disadvantages of each of these techniques are highlighted in relation to analysis of total arsenic and speciation of arsenic compounds in human urine which would be of particular benefit to those new to the field of arsenic speciation of urine samples. The review summarises our current understanding of arsenic metabolism through the analysis of urine samples and provides a list of arsenic species that have been identified in urine samples. This is done by focusing on recent published reports on arsenic metabolism and toxicity in relation to most investigated issues, i.e. genetics/ethnicity, ingestion and exposure.